Patients Satisfaction towards Health Service at the Out-patient Department of Hospital National Guido Valadares (HNGV), Timor-Leste. - Santiago Jorge Pereira; Charuwan Tadedej; Jutatip Sillabutra; Santawan Asavaroengchai (Rifa'Institute, 2022)
This study aimed to assess patient’s satisfaction towards health services at the Out-Patient Department of Hospital National Guido Valadares (HNGV) Timor-Leste. The research design was a cross-sectional study. Collected data from 206 outpatient consuming the OPD services at Hospital National Guido Valadares (HNGV), Timor-Leste, using interview method with structured questionnaire. Descriptive statistics and Chi-square test were used to analyze general, enabling factors, the need factors and association between satisfaction levels. Overall patient’s satisfaction was 77%. Patients had high satisfaction and low satisfaction were 55.8% and 44.2% respectively. The four components; convenience (85.4%), courtesy (64.6%), quality of care (55.8%) and only physical environment (47.6%) was low satisfaction. Regarding patients’ attitude was associated with satisfaction level (p-value = 0.001), more than half of patients (50.5%) had good attitude while less than half of them (49.5%) had poor attitude. Overall expectation was associated with satisfaction level (p-value = 0.001), patients with high expectation had high satisfaction (81.9%) and only (28.7%) of patient had low expectation. The health care service is the important part which should be improved by the hospital because it is the basic of service. Good or bad of health care service can influence the level of satisfaction. The hospital should improve the physical environment including; the atmosphere of this OPD should be clean, sitting chairs should be available at the waiting area and if possible arrange the television program to give health information in the sitting area, sign and directions to indicate where to go in the service should be complete and clear.